2005
DOI: 10.1111/j.1467-7652.2005.00146.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐lysine corn produced by the combination of enhanced lysine biosynthesis and reduced zein accumulation

Abstract: SummaryCorn is one of the major crops in the world, but its low lysine content is often problematic for animal consumption. While exogenous lysine supplementation is still the most common solution for today's feed corn, high-lysine corn has been developed through genetic research and biotechnology. Reducing the lysine-poor seed storage proteins, zeins, or expressing a deregulated lysine biosynthetic enzyme, CordapA, has shown increased total lysine or free lysine content in the grains of modified corn plants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
82
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 30 publications
4
82
1
3
Order By: Relevance
“…A number of transgenic approaches involving modiWcation of zein levels have been explored as well (Huang et al 2004(Huang et al , 2005Lai and Messing 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A number of transgenic approaches involving modiWcation of zein levels have been explored as well (Huang et al 2004(Huang et al , 2005Lai and Messing 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Attempts have also been made to reduce the content of these storage proteins by genetic engineering, using constructs designed to reduce their expression in seeds (Segal et al, 2003;Huang et al, 2005Huang et al, , 2006. Interestingly, specific reduction of zeins by this approach also causes an opaque phenotype (Segal et al, 2003), implying that this phenotype is directly associated with the reduction of zein storage proteins.…”
mentioning
confidence: 99%
“…Previous studies have reported on the production trials of transgenic plant that accumulate essential amino acid such as lysine, methionine, and tryptophan, since plants containing elevated levels of these amino acids could serve as important sources of animal food (Huang et al 2005;Shen et al 2002;Tozawa et al 2001). We have indicated that enhancement of the photorespiratory pathway via overexpression of glutamate: glyoxylate aminotransferase (GGAT ) gene leads to a hyperaccumulation of serine and glycine (Igarashi et al 2006).…”
mentioning
confidence: 99%